(untitled) (De Rebus Antiquis, 2020)
The work of Claudius Claudianus has been meticulously analyzed by leading researchers. It is opportune, however, to carry out a new critical reading that allows contributions to the understanding of the political intentions of his writings. This study seeks to interpret the fundamental ideas of the poet in relation to those he considered true enemies of Rome.